Eurasian Strategy in the Politics of Modern Russia - Yu. V. Sablina (Управленческое консультирование)
This article discusses the strategy of Russia in international cooperation on the Eurasian continent, through participation in the EAEU. The main problems of integration within the EAEU are identified. Integration processes on the Eurasian continent and Russia’s position in the emerging regional struggle for dominance over Eurasia in the third Millennium are considered. It is shown that through multilateral associations Russia plans to strengthen its role in Eurasian integration.